One damn thing after another : memoirs of an attorney general - Barr, William Pelham, 1950- (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2022)
"William Barr's first tenure as attorney general under President George H.W. Bush was largely the result of chance, while his second tenure under President Donald Trump a deliberate and difficult choice. In this candid memoir, Barr takes readers behind the scenes during seminal moments of the 1990s, from the LA riots to Pan Am 103 and Iran Contra. Thirty years later, Barr faced an unrelenting barrage of issues, such as Russiagate, the COVID outbreak, civil unrest, the impeachments, and the 2020 election fallout"--
Prologue -- Part I Early years. Planning ahead ; A shift in plans -- Part II Bush years. Top egghead ; Second in command ; Leading the department ; A whirlwind year -- Part III Interlude. Return to civilian life -- Part IV Trump years. Introduction ; Foreign schemes and domestic lies ; Into the storm ; One thing done, another begun ; Eating grenades ; "I believe you'll be impeached" ; Upholding fairness, even for rascals ; Bringing justice to violent predators ; Fighting the drug cartels ; Securing religious liberty ; Protecting national security ; Taking on Big Tech ; Facing the COVID pandemic ; Cops, race, and the big lie ; Protest and mayhem ; Trump vs. Trump ; Election and aftermath.
Includes index.
109913
Keywords: Barr, William Pelham, -- 1950-; United States. -- Department of Justice. -- Office of the Attorney General -- Officials and employees -- Biography; 1981-2021; Attorneys general -- United States -- Biography; Employees; Politics and government; Autobiographies; Biographies